Language learning strategies and Croatian EFL learners - Mihaljević-Djigunović, Jelena (1999)
The article describes a study of the language learning strategies used by Croatian EFL learners. The study was carried out on 362 subjects of different age, gender and profieciency level. The Croatian translation of Oxford's SILL Version 5.1 was used to assess the strategies. The results described in the paper show that Croatian learners' strategy use was in the medium range, that females used strategies more often than males and that strategy use correlated with EFL achievement. Instead of using the six-part division established by Oxford, the author carried out a factor analysis procedure in an effort to capture better the dynamics of the SILL data of her specific sample. The isolated factors revealed the following types of strategies: memory, communicative, metacognitive, cognitive, comprehension and socioaffective strategies.
Projekt MZOS
ENG